Peran Zending dalam Pelayanan Kesehatan di Tarutung, 1900-1942 - Cici Christina Manurung (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This article aims to explain how the history of the development of health facilities in Tarutung in the 20th century. Tarutung in the past was used as the center of the Christianization movement by zendings from various countries. One of the zending organizations that plays a big role in health services in Tarutung is a German zending organization called Rheinische Missionsgesellscaft (RMG). This article uses a historical research method with four stages in its writing, namely: heuristics (collection of sources), verification (source criticism), interpretation, and historiography (writing). The results showed that zending plays a big role in improving the health and hygiene of the Batak people in Tarutung. The zendings also introduced modern methods of medicine that replaced traditional medicine by the Batak datu. In addition, zending also played a role in establishing various health facilities in Tarutung such as: hospitals, auxiliary hospitals, polyclinics, and nursing and midwifery schools.